Substituted α‐Sulfur Methyl Carbanions: Effective Homologating Agents for the Chemoselective Preparation of β‐Oxo Thioethers from Weinreb Amides. Issue 20 (26th April 2018) - Senatore, Raffaele; Ielo, Laura; Urban, Ernst; Holzer, Wolfgang; Pace, Vittorio
Abstract : The proper generation of α‐thiomethyllithium reagents via reductive lithiation or deprotonation followed by reaction with variously functionalized Weinreb amides represents an excellent method to access β‐oxo thioethers. The procedure is adaptable to alkyl‐ or aryl‐ thiomethyllithium conjugates. It has the advantages of conceptual simplicity and versatility of the addition of organometallics to Weinreb amides with the possibility to fully preserve the optical information contained in the starting materials. Abstract : A simple method to access β‐oxo thioethers by reductive lithiation or deprotonation followed by reaction with Weinreb amides has been developed. The method is applicable to alkyl‐ or aryl‐ thiomethyllithium conjugates.